2012
DOI: 10.5603/fhc.2012.0005
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal changes in testicular development and androgen receptors immunolocalization in D’Man ram lambs

Abstract: Abstract:The purpose of this study was to characterize testicular development in D'Man ram lambs, focusing primarily on androgen receptors (ARs) immunolocalization in the adenohypophysis and testis that is not still known in the D'Man ram lamb. Lambs (n = 12) were divided into four groups (three lambs per group). Adenohypophysis and testis were fixed and paraffin-embedded; cross-section (3 μm) were stained and evaluated with immunohistochemistry. Testis weight increased at a greater rate between two and five m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, some investigators demonstrated that nuclear ARs were detectable by immunohistochemistry in germ cells in human and animal testes [13,29,32]. The cytoplasmic localization of AR was shown in elongated spermatids in the adult rat testis [33], Leydig cells of patients with Klinefelter's syndrome [34], and in mice with a Sertoli cells-specific knock-out of the connexin 43 gene [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, some investigators demonstrated that nuclear ARs were detectable by immunohistochemistry in germ cells in human and animal testes [13,29,32]. The cytoplasmic localization of AR was shown in elongated spermatids in the adult rat testis [33], Leydig cells of patients with Klinefelter's syndrome [34], and in mice with a Sertoli cells-specific knock-out of the connexin 43 gene [35].…”
Section: Discussionmentioning
confidence: 99%